2016
DOI: 10.1002/ijc.30483
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid derivatives exert a potent anti-myeloma activity bothin vitroandin vivo

Abstract: Although hematopoietic and immune system show high levels of the cannabinoid receptor CB2, the potential effect of cannabinoids on hematologic malignancies has been poorly determined. Here we have investigated their anti-tumor effect in multiple myeloma (MM). We demonstrate that cannabinoids induce a selective apoptosis in MM cell lines and in primary plasma cells of MM patients, while sparing normal cells from healthy donors, including hematopoietic stem cells. This effect was mediated by caspase activation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…Recently, interest in the EC system emerged for another hematological malignancy, multiple myeloma (MM). Indeed, it was shown that plasma cells expressed high levels of CB2 and that cannabinoid derivatives selectively induced apoptosis in MM cell lines and primary plasma cells from MM patients [23], similarly to what previously reported for AML [29]. Hence, the EC system in these malignancies might represent a potential target for therapeutic exploitation.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Recently, interest in the EC system emerged for another hematological malignancy, multiple myeloma (MM). Indeed, it was shown that plasma cells expressed high levels of CB2 and that cannabinoid derivatives selectively induced apoptosis in MM cell lines and primary plasma cells from MM patients [23], similarly to what previously reported for AML [29]. Hence, the EC system in these malignancies might represent a potential target for therapeutic exploitation.…”
Section: Introductionsupporting
confidence: 75%
“…Interestingly, ECs have been recently found to modulate hematopoiesis, including megakaryocyte maturation, thrombopoiesis, and platelet aggregation, as well as chemokine release and migration of immunocompetent cells [15,[20][21][22]. Importantly, blood cells and platelets act as sources of ECs, whereas various hematopoietic cell subsets, particularly B-cells, display high levels of CB2 [23]. In addition, ECs released by platelets are involved in thrombogenic processes [24].…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that THC (tetrahydrocannabinol) caused an increase in ceramide levels through de novo synthesis, which led to apoptosis in C6 glioma cells. This increase of ceramide levels through THC or other cannabinoids was also shown in prostate and colon cancer cells, as well as mantle cell lymphoma (MCL) and multiple myeloma (Barbado et al, 2017; Cianchi et al, 2008; Gustafsson, Christensson, Sander, & Flygare, 2006; Mimeault, Pommery, Wattez, Bailly, & Henichart, 2003). Further work in MCL showed that cannabinoids induced CerS3 and CerS6 expression.…”
Section: Effects Of Chemo- and Radiation Therapieson Sphingolipidsmentioning
confidence: 69%
“…WIN55,212-2, a CB1R/CB2R dual agonist, has been one of the most widely used pharmacological tools to get insights into the endocannabinoid system. WIN55,212-2 ( Table 1 ) inhibits cell proliferation and migration in triple-negative breast cancer (Qamri et al, 2009); in prostate cancer (Morell et al, 2016); in gastric cancer (Xian et al, 2016); in hepatocellular carcinoma (Xu et al, 2015); in lung cancer, testicular cancer, and neuroblastoma (Müller et al, 2017); in myeloma (Barbado et al, 2017); and in renal carcinoma (Khan et al, 2018). Most of these results were confirmed in vivo in various mouse model systems.…”
Section: Cannabinoids With Anticancer Potentialmentioning
confidence: 99%